Weavers Malaysia: business plan / Fakrul Azzim Abdullah … [et al.] - Abdullah, Fakrul Azzim; Mohd Nazir, Nazrin Syazwani; Safar, Syazwanie; Abd Gani, Nur Aina Shuhada; Mohd Rafie, Nur Izzatul Syahirah (2022)
This assignment focuses on creating a social business in Malaysia. Our group had chosen to create a website business namely Weavers Malaysia. This business is based on websites all around the world, especially in Malaysia. The physical office is located at Kampung Baharu, 26060 Kuantan, Pahang. Our business offers a service which is a trip for people to the songket factory, and we also help the songket weaver to promote their songket product on our website. This business is a partnership business and only has four employees. This business was led by Fakhrul Azzim and his team which are Izzatul Syahirah, Syazwanie, Nazrin, and Aina. The main focus of this business is to introduce songket throughout the state and abroad as well as to elevate songket as the country’s traditional wears. Weavers Malaysia want to promote the art of songket to the public and help the songket traders and weavers to grow their business. This business also wants to help weavers generate income by supplying quality songket according to customer tastes and preferences. Weavers Malaysia do the trip activity at Kuantan, Pahang due to that state being famous with the songket product and the quality of the songket is very nice and smooth. This can attract more people to come and support the songket product. Our business target market are students, family, tourists, and also teenagers. This business is operated every day except Wednesday. All of the customers will book their date and time to go to the songket factory trip not only at the office, but also can book and buy trip tickets through the website. This will make it easier for our customers to get and use our service. Besides that, Weavers Malaysia has a lot of advantages to compete with other competitors such as EXO travel, Al Masyhur International Travel & Tour Sdn. Bhd. (AMI Travel) and Star Travel. All of our employees have good communication and skills in serving customers to make sure that our customers will not be dissatisfied when using our service. We also use social media platforms such as TikTok, Twitter and Instagram to promote our business and use the 5G high speed internet network to avoid any internet problems and make it easy for our customers to use our website. When compared to other competitors, our company offers a wide range of trip packages at reasonable pricing. All of our customers are also provided with easy transportation by our company. We also have a meal package, so that our customers don't have to buy food on their own throughout the trip. This business finance is through the personal contributions of RM10,000 apiece from the partners and RM100,000 of bank loan to start-up the business capital and costs. All of us are hoping that our business will grow bigger not only well-known in Malaysia, but also all around the world and can gain a high profit every year.